Cost variation analysis of different brands of commonly prescribed antihypertensive drugs, available in Indian market: a pharmacoeconomic study - Mir, Shakeel Ahmad (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Worldwide, Hypertension is estimated to cause 7.5 million deaths, about 12.8% of the total of all deaths. This accounts for 57 million disability adjusted life years (DALYS) or 3.7% of total DALYS. Globally, the overall prevalence of hypertension in adults aged 25 and over was around 40% in 2008.Despite its benefits, treatment of hypertension is costly. Direct medical spending to treat hypertension totalled $42.9 billion in 2010, with almost half ($20.4 billion) in the form of prescription medications. Being, a silent disease, adherence to antihypertensive drugs is poor. One of the important factors of poor adherence to antihypertensives is the cost of the drugs. There is wide cost variation among different brands of the same antihypertensive drug. Clinician’s awareness of cost of therapeutics is poor. The costly brand of same generic drug is proved to be in no way superior to its economically cheaper counterpart. Methods: The minimum and the maximum cost in Rupees (INR) of a particular antihypertensive agent manufactured by various pharmaceutical companies in the same strength were noted. The cost of 10 tablets/capsules was calculated. The cost ratio and percent cost variation were calculated for each brand. Results: The cost variation observed in the present study was as high as 2337.50 % for Hydralazine. Other significantly high cost variations found in the present study were: 1315.25% (Telmisartan+Hydrochlorthiazide), 870.58% (Amlopdipine), 558.34% (Amlodipine+Atenolol), 537.68% (Valsartan), 394.44% (Metoprolol), 344.44% (Enalapril), 316.22% (Propranolol), 300% (Lisinopril), 290.90% (Carvedilol), 289% (Cilnidipine), 271.99% ( Labetolol), 268.04% (Indapamide), 256.31% (Losartan), 255.19% (Irbesartan), 226% (Methyldopa), 223.04% (Frusemide), 209.78% (Nitrendepine), 192.08% (Terazosin), 189.25% (Atenolol), 142.42% (Bisoprolol) and 120.51% (Felodipine). Conclusions: Financial constraints are a reality in almost all aspects of medicine. Doctors must consider drug costs to their patients. Increasing pharmaceutical costs negatively impacts patients. Given the increasing healthcare costs, there is growing interest in rational prescribing, which takes costs of medication into account.